PENGARUH KEBIJAKAN DIVIDEN, PROFITABILITAS, DAN LEVERAGE TERHADAP NILAI PERUSAHAAN - Toto Rahardjo; Qomarotul Badriyah (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
The food and beverage sub-sector companies have experienced a decline in stock prices, especially in 2020. The value of the company describes the level of welfare of the shareholders. The high and low value of the company can be seen from the company's stock price. The objective of this research is to identify the effects of dividend policy, profitability, and leverage on firm value. This quantitative research uses secondary data concerning companies in the sub-sector of food and beverages listed on the Indonesia Stock Exchange in the period of 2014-2020. The samples were selected using purposive sampling technique with several criteria. The population in this study uses 28 annual reports of food and beverage sub-sector companies and 7 companies that meet the criteria in determining the sample. Since multiple regression was used in this study, classical assumption test was also performed. The results of this study indicate that dividend policy has a positive effect on firm value. Profitability has a positive effect on firm value. Leverage has a positive effect on firm value. Therefore, companies must pay attention to their dividend payout ratio, profitability, and leverage in order to improve their values.